Implementasi Smart Governance Dalam Pelayanan Administrasi Kependudukan Di Kota Surabaya (Studi Kasus: Di Kecamatan Benowo) - Fitriana, Lilis; Arif, Lukman (Peneliti.net, 2024)
ABSTRACT The Surabaya City Government implements smart governance in organizing population administration services through the Surabaya Civil Registration and Population Agency (Dispendukcapil Kota Surabaya). In the implementation of the smart government concept, Dispendukcapil Kota Surabaya has created an innovation in the form of a website called Klampid New Generation (KNG). The main objective of this research is to analyze the implementation of smart governance in population administration services in Surabaya City, with a case study focus on Benowo Subdistrict, Surabaya. This study adopts a qualitative descriptive method, utilizing primary data obtained through observation, documentation, and interviews. Secondary data is also collected from articles, journals, previous research, and official websites. The results of this research indicate that the implementation of smart governance in population administration services in Surabaya City is considered successful, aligning with the implementation theory that involves elements such as communication, resources, disposition, and bureaucratic structure as determinants of success. However, the researcher recommends that Dispendukcapil Kota Surabaya further optimize the communication aspect. Keywords: population administration, implementation, smart governance